A Rare Case Report of Mid Cavitary Takotsubo: The Role of Magnetic Resonance Imaging. (15th September 2011) - Sherratt, Jesse; McDonald, Carolyn E.; York, Gerald; Slim, Ahmad
Abstract : This is a case report of a female presenting originally with clinical picture of acute coronary syndrome and depressed left ventricular function with no angiographic evidence of coronary artery disease with mid cavitary akinesis and basal as well as apical hyperkinesis after emotional stresses identified by multi-imaging modalities to be mid cavitary Takotsubo. The Incidence and the prevalence of apical ballooning syndrome (Takotsubo) is on the rise with more reports in the literature; however, mid cavitary Takotsubo remains rare and raises questions more than answers as to the reason behind the mid cavitary localization in some patients versus apical involvement.